Automotive online sales in Europe: a supply and demand analysis - Caron, Carolina Luisa Von (2022)
The rise of e-commerce has reached the automotive industry and spurred online sales of cars. This study conducts a supply and demand analysis of automotive online sales across Europe. For this, the advancements of car manufacturers are investigated and matched with the demand of customers. The study finds that car manufacturers are starting to move online but few offer a comprehensive online customer experience yet. Customers, however, already conduct substantial parts of their journey online and increasingly demand online sales. Recommendations for car manufacturers are derived on how to advance online to satisfy these customer demands and ensure future competitiveness.